Seroprevalence of Anti-Rubella IGg Antibody Among Pregnant And Childbearing Women in Diyala Province-Iraq - SH. Hasan , Abdul-Razak (Diyala Journal of Medicine, 2019)
Background: In countries where the rate of susceptible women to rubella infection is higher than 10%, preconceptional or prenatal screening is important to reduce the burden of the disease. Objectives: determination of anti-rubella IgG seropositivity and susceptibility rates among pregnant and childbearing women in Baquba-Diyala province. Subjects and methods: A total of 184 women were enrolled in the present study which was conducted in Baquba-Diyala province during the period from April/2007 to September/2008. Ninety eight pregnant women were chosen from those attending the primary health care centers in Baquba. They include 46(46.9%) who had previous abortions with a mean age 27.2 ± 5.3 years, and 52(53.1%) without previous abortion with mean age 23.7± 5.1 years. Additionally, 86 non-pregnant childbearing women were enrolled as a control group. Of those, 39(45.3%) had previous abortion with mean age 33.5 ± 7.8 years, and 47 (54.6%) without previous abortion, the mean age 30.7±7.8 years. Certain demographic factors were collected by personal interview. Anti-rubella IgG specific antibody were detected by enzyme-linked immunosorbant assay (ELISA). Data were statistically analyzed using SPSS version 13 computer assisted program. P value of < 0.05 was considered significant. Results: The results revealed that the IgG seropositivity among pregnant women without previous abortion, and those with previous abortion was 96.1% and 76% respectively, with a statistically significant difference (p=0.04). The seropositivity among non-pregnant women without previous abortion, and those with previous abortion was 85.1% and 100% respectively, with a statistically insignificant difference (p= 0.11). The overall susceptibility rate for rubella infection was 10.7%. There was insignificant effect of age, educational levels, residency, presence of pregnancy, and history of previous abortion on the seropositivity rate of IgG specific anti- rubella antibody. Conclusion: evaluation of the susceptibility of women in the reproductive age to rubella infection is essential to set a strategy for prevention of congenital rubella syndrome.